(untitled) (Jurnal Teknologi Industri Pertanian, 2022)
Edible oils as essential fatty acids sources, such as linolenic acid, eicosapentaenoic acid, and docosahexaenoic acid, are commonly extracted from plants and seafoods, particularly fish. The productionof fish oil has several drawbacks, including overfishing issues, mercury contamination, and unpleasant smell of fish. Oil production from plants requires extensive land used, long harvest time, and high operational costs. Single-cell oils from microorganisms are the solution to overcome these problems. Therefore, this study aimed to explore the potential of microorganisms, i.e. microalga and yeast, which had previously been isolated from mangrove forests in Aceh Province, Indonesia, as sources of essential fatty acids. Two types of microorganisms used were Thraustochytrium multirudimentale and Rhodotorula mucilaginosa. The results showed that the highest amount of oil was extracted from yeast (17.04 ± 0.78 mg/g), while microoalga produced 4.50 ± 0.49 mg/g only. Based on correlation analysis, the optical density (OD) and biomass, had good correlation with r = 0.990. The spectra of FT-IR analysis from microalga and yeast oils proved that both contained C=O groups which identified as esters of fatty acids and C=C groups identified as unsaturated fatty acids. Thraustochytrium multirudimentale and Rhodotorula mucilaginosa are potential as single-cell oil sources containing essential fatty acids. Keywords: essential oil, fatty acids, microalgae, omega-3, single-cell oil, yeast